Cities Hosting Holy Shrines: The Legacy of Pilgrimage and Its Impact on Urban Form - Maroufi, Hossein; Rosina, Elisabetta (ICONARCH International Congress of Architecture and Planning, 2017)
This paper explores pilgrimage in the context of historic holy cities which contain at least one religious complex through which the ritual of pilgrimage takes place. One controversial tension in urban development process of holy cities is the tension between urban growth, on the one hand, and adapting city structure to the needs of pilgrims on the other hand. This paper investigates this issue by referring to experiences of two major holy cities in of Mecca and Mashhad. Both cities are spiritual centers which host millions of pilgrims throughout year. The aim of this paper is to analyze the process of city center transformation in both cities and monitor different policies and interventions that shaped their morphologies up to now. Through historical analysis of urban form, flow of pilgrims has affected the morphology of both cities in similar ways. Accordingly policies and interventions by local officials have shaped the urban center in three similar ways: enlargement and expansion of shrine, vehicular access to shrine, and real-estate speculation. İn the absence of protective and preventive codes and policies both Mecca and Mashhad have lost their historical urban fabric and their cultural patrimonies. Their traditional urban scape and prominence of shrine has been substituted by high rise mega projects. İn a similar way their local crafts and small-scale retails have been replaced by global retail chain.